Jian zi ru mian / Lin Huiyin zhu. - Liu, Na (Beijing : Tai hai chu ban she, 2022)
The book contains 31 correspondence. These letters come from women of different ages, who pour out their life problems from the perspective of their original family, intimate couple, mother-in-law relationship, etc. The author answered these questions in his reply. She did not complain to others with the letter, but from the perspective of a daughter, wife and mother, she analyzed the root causes of negative emotions and taught specific countermeasures so that those trapped in them gain courage and strength, regain self-confidence, and live a happy life.
Keywords: Chinese letters -- 20th century; Chinese Etymology